Infective Endocarditis by Lactobacillus Species-A Narrative Review - Petros Ioannou; Afroditi Ziogou; Ilias Giannakodimos; Alexios Giannakodimos; Stella Baliou; George Samonis (MDPI AG, 2024)
Bacteria of the genus Lactobacillus are microaerophilic or aerotolerant anaerobic Gram-positive non-spore-forming rods. They are considered essential members of the human gut microbiome; however, recent studies have revealed that these microorganisms are less predominant in the gut microbiome than initially thought. Lactobacillus spp. is mainly known for its use as a probiotic in foods and supplements to prevent and treat specific issues such as infectious diseases, irritable bowel syndrome, and diabetes mellitus. However, Lactobacillus spp. may occasionally cause infections such as bacteremia or infective endocarditis (IE). The present study aimed to review all cases of IE by Lactobacillus spp. and describe the epidemiology, microbiology, clinical characteristics, treatment, and outcomes of this infection by collecting relevant data from studies existing in Pubmed and Scopus until 28 September 2023. A total of 77 studies containing data for 82 patients were included. The median age was 56 years, and 69.6% were male. A prosthetic valve was present in 16% of patients, and 17.3% had previously been on probiotics. The aortic valve was the most commonly involved intracardiac site, followed by the mitral valve. Fever, embolic phenomena, sepsis, and heart failure were the most common clinical presentations. Aminoglycosides and penicillin were the most commonly used antimicrobials for definitive treatment. Surgery was performed in 53.7% of patients. Overall mortality was 17.1%. IE in prosthetic valves and presentation with shock were independently associated with overall mortality.